PENGARUH PENERAPAN BAGASI BERBAYAR TERHADAP KEPUASAN PENUMPANG MASKAPAI WINGS AIR DI BANDAR UDARA H. HASAN AROEBOESMAN ENDE - Tenda, Khairunnissa Fitria; Putrie, Annike Resty (Sekolah Tinggi Teknologi Kedirgantaraan, 2024)
Wings Air (PT Wings Air Abadi) is a domestic airline based in Jakarta, Indonesia. Wings Air has won the trust of air transportation users with its Low Cost Carrier and can accompany transportation users to routes that are not covered by other airlines. On 8th January 2019 Lion Air implemented new regulations by removing checked baggage services for domestic Wings Air flights. Regarding this policy, passengers only get free cabin baggage facilities with a maximum weight of 7 kg and one personal item such as a laptop bag, hand bag, with maximum cabin baggage dimensions of 40 cm × 30 cm × 20 cm. In this article, we will examine the effect of implementing paid baggage on Wings Air passenger satisfaction at H. Hasan Aroeboesman Ende Airport. The research was conducted quantitatively. Data collection was carried out by conducting a literature study of the results carried out by previous researchers, taking from the documentation that had been created, and using questionnaire techniques. Validity test, reliability test, hypothesis test, T test, simple linear regression test and coefficient of determination were carried out in analyzing the data obtained. The results show that Ha is accepted and Ho is rejected. This means that there is an influence of the application of paid baggage on the satisfaction of Wings Air airline passengers at H. Hasan Aroesboeman Ende Airport. This is proven by the value of tcount (i.e. 33.248) > ttable (i.e. 1.984) with a significance of 0.000 (or < 0.05) in hypothesis testing. The coefficient of determination test produces an R square of 0.919 (or 91.9%), which means it is true that paid baggage is a variable that is strongly related to passenger satisfaction.